الإسلام وفكرة الضمان الاجتماعي - د. عمر إبراهيم حسين (Aljameai, 2022)
الملخص:اهتم الباحثون المسلمون بمحاولة اثبات ان الاسلام قد سبق الانظمة الضمانية الحديثة، في تأصيل فكرة الحماية الاجتماعية، وصاروا يطلقون مصطلح الضمان الاجتماعي الإسلامي، الذي يعكسه التكافل الاجتماعي في كل ادوار ومراحل الدولة الاسلامية، ويقوم على أسس ترسخها الآيات القرآنية والاحاديث النبوية الشريفة، هذا ما يؤكد الرحمة و التعاون جوهرا فكرة الضمان الاجتماعي، فالدين الاسلامي هو دين الضمان الاجتماعي من حيث التزام الدولة واما من حيث التزام الافراد فهو دين التكافل ، والضمان الاجتماعي في الإسلام له خصائص من حيث ان الحاجة مناطه ويغطي بحمايته كل المحتاجين مسلمين او غير مسلمين ويتسع نطاقه، وللعمل اولوية فيه وتساهم الجماعة والافراد في تغطية منافعه.Abstract:                                                                                               Muslim researchers were interested in trying to prove that Islam had preceded modern security systems, in rooting the idea of ​​social protection, and they began to use the term Islamic social security, which is reflected in social solidarity in all the roles and stages of the Islamic state, and is based on foundations rooted in the Qur’anic verses and the honorable prophetic hadiths, this confirms Mercy and cooperation is the essence of the idea of ​​social security. The Islamic religion is the religion of social security in terms of the state’s commitment, but in terms of the commitment of individuals, it is a religion of solidarity, and social security in Islam has characteristics in that the need is entrusted to it and it covers all the needy, Muslims or non-Muslims, and expands its scope, and for work It is a priority and the group and individuals contribute to covering its benefits.